Physical Conditions of Fast Glacier Flow: 2. Variable Extent of Anisotropic Ice and Soft Basal Sediment From Seismic Reflection Data Acquired on Store Glacier, West Greenland. Issue 2 (24th February 2018) - Hofstede, C.; Christoffersen, P.; Hubbard, B.; Doyle, S. H.; Young, T. J.; Diez, A.; Eisen, O.; Hubbard, A.
Abstract : Outlet glaciers of the Greenland Ice Sheet transport ice from the interior to the ocean and contribute directly to sea level rise because discharge and ablation often exceed the accumulation. To develop a better understanding of these fast‐flowing glaciers, we investigate the basal conditions of Store Glacier, a large outlet glacier flowing into Uummannaq Fjord in west Greenland. We use two crossing seismic profiles acquired near the centerline, 30 km upstream of the calving front, to interpret the physical nature of the ice and bed. We identify one notably englacial and two notably subglacial seismic reflections on both profiles. The englacial reflection represents a change in crystal orientation fabric, interpreted to be the Holocene‐Wisconsin transition. From Amplitude‐Versus‐Angle (AVA) analysis we infer that the deepest ∼80 m of ice of the parallel‐flow profile below this reflection is anisotropic with an enhancement of simple shear of ∼2. The ice is underlain by ∼45 m of unconsolidated sediments, below which there is a strong reflection caused by the transition to consolidated sediments. In the across‐flow profile subglacial properties vary over small scale and the polarity of the ice‐bed reflection switches from positive to negative. We interpret these as patches of different basal slipperiness associated with variable amounts of water. Our results illustrate variability in basal properties, and hence ice‐bed coupling, at a spatial scale of ∼100 m, highlighting the need for direct observations of the bed to improve the basal boundary conditions in ice‐dynamic models. Key Points: Two high‐resolution seismic reflection profiles were acquired 30 km upstream of the calving front at the center flow line of Store Glacier, a fast‐flowing tidewater glacier draining the western sector of the Greenland ice sheet Analysis reveals an 80 m thick layer of anisotropic, horizontally easily deformable basal ice, overlying 45 m unconsolidated sediments which rest on a sequence of hard consolidated sediments Spatial variability of basal anisotropic ice and subglacial material imply different subglacial deformation mechanisms, that is, Coulomb‐type of plastic deformation and a Weertman‐type of sliding